Analisis Keterhubungan Tingkat Kemiskinan Dan Pembiayaan Syariah Di Indonesia Tahun 2005-2020 - Agustin Nengsih, Titin; Kurniawan, Bambang; Fitri Harsanti, Eka (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2021)
Poverty is one of the main problems experienced by almost all countries in the international world. Ongoing poverty in developing countries is usually indicated by presence, backwardness, and ultimately waiting. In Indonesia, until now poverty is still an important problem for the government that must be completely resolved. The purpose of this study was to determine and examine the effect of Islamic financial institution financing on mission problems in Indonesia in 2005–2020. The form of research used in this study is a quantitative descriptive technique with Simple Linear Regression analysis. The type of data used in this study is time set data from 2005–2020. The hypothesis test in this test uses Simple Linear Regression evaluation and it is found that financial institutions have a considerable influence on the poverty level in Indonesia with a significance price of 0.000 with a coefficient of determination of 81% and affects other variables outside the study.